Patient profile and comparison of three diagnostic criteria for cardiac sarcoidosis in a tuberculosis endemic population - Pattnaik, Bijay; PB, Sryma; Verma, Mansi; Kumar, Sanjeev; Arava, Sudheer; Mittal, Saurabh; Tiwari, Pavan; Hadda, Vijay; Mohan, Anant; Guleria, Randeep; Madan, Karan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: Cardiac sarcoidosis (CS) is an underdiagnosed and life-threatening condition. Histopathological diagnosis is difficult due to the risks and variable diagnostic yield of endomyocardial biopsy.Objectives: To compare three diagnostic criteria for the diagnosis of CS before initiating immunosuppressive therapy.Methods: A retrospective review of the Sarcoidosis database (375 patients) was performed to identify patients with CS. Demographic and clinical details were retrieved. We applied the available diagnostic criteria for the diagnosis of CS: The World Association of Sarcoidosis and Other Granulomatous Diseases (WASOG), Heart Rhythm Society (HRS), and Japanese Ministry of Health and Welfare (JMHW) criteria.Results: Out of 375 patients, 15 (4%) were identified with CS. The mean age was 42.8 years and 53% were female. The most common symptoms were breathlessness, palpitation, and fatigue in 80%, 53.3%, and 46.6% patients respectively. Tuberculin positivity (≥ 10mm induration) was seen in 26.6%. 80% and 53.3% of the patients had abnormal ECG and 2D-echocardiography findings, respectively. Six patients had a history of Ventricular tachycardia (40%). LV Ejection fraction was reduced in 11 subjects (73.3%). Cardiac-MRI showed late gadolinium enhancement in 53.3%. A definitive histopathological diagnosis was established in 86.6% (13/15) patients. Of the 15, all satisfied JMHW criteria and WASOG criteria (12 (80%) at least probable category, 3 (20%) possible CS), and 13 (86.6%) met HRS criteria for a diagnosis of CS.Conclusion: Histopathological diagnosis can be established in a majority of patients with CS in tuberculosis endemic settings. JMHW and WASOG criteria perform equally well in TB endemic settings.